2016
DOI: 10.1016/j.cellsig.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A crosstalk between TGF-β/Smad3 and Wnt/β-catenin pathways promotes vascular smooth muscle cell proliferation

Abstract: Rationale Endovascular interventions performed for atherosclerotic lesions trigger excessive vascular smooth muscle cell (SMC) proliferation leading to intimal hyperplasia. Our previous studies show that following endovascular injury, elevated TGF-β/Smad3 promotes SMC proliferation and intimal hyperplasia. Furthermore in cultured SMCs, elevated TGF-β/Smad3 increases the expression of several Wnt genes. Here we investigate a crosstalk between TGF-β/Smad3 and Wnt/β-catenin signaling and its role in SMC prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 43 publications
3
69
2
Order By: Relevance
“…These studies show that SMC β-catenin is dispensable for the maintenance of uninjured adult vessels, but is required for neointimal formation after vascular injury. Moreover, β-catenin is required for expression of a set of genes reported to promote SMC invasion and neointimal growth, including matrix metallopeptidase 2 (Mmp2), and is necessary for SMC invasion in vitro ; this complements the pro-proliferative and pro-survival roles of SMC β-catenin previously reported 69, 16, 18, 21 . Finally, we found that inhibitors of β-catenin effectively reduced growth of mouse and human vascular SMCs in culture.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…These studies show that SMC β-catenin is dispensable for the maintenance of uninjured adult vessels, but is required for neointimal formation after vascular injury. Moreover, β-catenin is required for expression of a set of genes reported to promote SMC invasion and neointimal growth, including matrix metallopeptidase 2 (Mmp2), and is necessary for SMC invasion in vitro ; this complements the pro-proliferative and pro-survival roles of SMC β-catenin previously reported 69, 16, 18, 21 . Finally, we found that inhibitors of β-catenin effectively reduced growth of mouse and human vascular SMCs in culture.…”
Section: Introductionmentioning
confidence: 66%
“…These studies show that 1) treatment of vascular SMCs in culture with recombinant Wnt2b, Wnt4, Wnt5a, or Wnt9a, but not Wnt11, increases β-catenin protein levels and cell proliferation 16 ; 2) treatment with recombinant Wnt2 increases Wisp1 mRNA levels and induces SMC migration 11 ; 3) balloon injury of carotid arteries in diabetic rats results in neointimal hyperplasia associated with increased Wnt4, Dvl-1, β-catenin, and cyclin D1 expression, and reduced p21 levels, a phenotype suppressed by up-regulation of microRNA-24 17 ; 4) aortas from rats fed a high-fat diet have increased numbers of SMCs and lipid droplets, associated with higher mRNA levels for Wnt3a, β-catenin, Tcf-4, and cyclin D1, suggesting a role for Wnt/β-catenin signaling in hyperlipidemia-induced SMC proliferation 18 ; and 5) in a model of Angiotensin II-induced arterial hypertension, complement C1q activates β-catenin signaling, which is required for vascular SMC proliferation 19 .…”
Section: Introductionmentioning
confidence: 74%
“…Wnt7a and Wnt9a were recently shown to stimulate β-catenin signaling (83,84). The two small-molecular Wnt inhibitors XAV939 and LGK974 suppressed Wnt/β-catenin signaling, significantly extended life span, ameliorated cystic phenotypes, and improved renal functions in our mouse model of Pkd2-associated ADPKD ( Figure 6 and Supplemental Figure 9).…”
Section: +mentioning
confidence: 93%
“…Previous studies have identified TGF β as a critical molecular mediator and SMCs as the major cellular effectors in this repairing process (Bobik ; DiRenzo et al. ). To evaluate the effect of SMC‐specific TGF β signaling on regulating NIH and wall remodeling, we deleted SMC TGF β type I receptors (i.e., Tgfbr1 iko ) and characterized the phenotype of Tgfbr1 iko FAs following endothelial denudation and intramural dilation.…”
Section: Discussionmentioning
confidence: 99%